Kajian Lingkungan terhadap Kerusakan Tanah Akibat Limbah Semen dari Perbedaan Sistem Pengadukan - Mustofa Mustofa; John Bimasri; Wartono Wartono (MAN 4 Kota Pekanbaru, 2026)
The rapid expansion of infrastructure development has increased concrete consumption, resulting in cement mortar waste that may contaminate soil and degrade its physical properties. This study analyzed the effects of cement waste from different concrete mixing systems on soil physical characteristics and identified the most environmentally sustainable mixing method. An experimental comparative study was conducted in F Trikoyo Village, Musi Rawas Regency, Indonesia, from May to June 2026. Four mixing systems were evaluated: direct mixing on the ground, mixing on a wooden platform, using a mini concrete mixer, and using a large concrete mixer. Soil bulk density, porosity, infiltration, permeability, and aggregate stability were analyzed through field observations and laboratory testing. Direct ground mixing generated the highest cement waste (9.55%), increasing bulk density by 33.90% while reducing porosity, infiltration, permeability, and aggregate stability by 26.63%, 62.93%, 77.90%, and 37.85%, respectively. In contrast, the large concrete mixer produced the least waste (1.18%) and caused minimal soil degradation. Therefore, large concrete mixers are recommended to reduce soil contamination and support sustainable construction practices.